The grand challenges of migration ecology that radar aeroecology can help answer. Issue 5 (26th November 2018) - Bauer, Silke; Shamoun‐Baranes, Judy; Nilsson, Cecilia; Farnsworth, Andrew; Kelly, Jeffrey F.; Reynolds, Don R.; Dokter, Adriaan M.; Krauel, Jennifer F.; Petterson, Lars B.; Horton, Kyle G.; Chapman, Jason W.
Abstract : Many migratory species have experienced substantial declines that resulted from rapid and massive expansions of human structures and activities, habitat alterations and climate change. Migrants are also recognized as an integral component of biodiversity and provide a multitude of services and disservices that are relevant to human agriculture, economy and health. The plethora of recently published studies reflects the need for better fundamental knowledge on migrations and for better management of their ecological and human‐relevant effects. Yet, where are we in providing answers to fundamental questions and societal challenges? Engaging a broad network of researchers worldwide, we used a horizon‐scan approach to identify the most important challenges which need to be overcome in order to gain a fuller understanding of migration ecology, and which could be addressed using radar aeroecological and macroecological approaches. The top challenges include both long‐standing and novel topics, ranging from fundamental information on migration routes and phenology, orientation and navigation strategies, and the multitude of effects migrants may have on resident communities, to societal challenges, such as protecting or preventing migrant services and disservices, and the conservation of migrants in the face of environmental changes. We outline these challenges, identify the urgency of addressing them and the primary stakeholders – researchers, policy makers and practitioners, or funders of research.